Visitor’s perspective of Patan Hospital, Patan Academy of Health Sciences, Nepal - Pawar, Aditya S; Brar, Baljeet (Journal of Patan Academy of Health Sciences, 2018)
A local man sits on the pavement in Patan Durbar Square at one am. A taxi driver calls a cell phone number I handed to him that belongs to the guesthouse I am staying at. Both of them are strangers to me, but go out of the way to make sure I reach home safe. It struck a chord, nice warm people and very hospitable. The next morning begins with meeting Mr. Shakya, the person in charge of visitors at Patan hospital, touring the hospital, including the outpatient department, emergency room, wards, auditorium, and medical school. I’m greeted with Namaste, and introduced as “tyo America ma doctor ho”. This is followed by a most important visit to the cafeteria. We go over the menu. I am told the most popular options and also advice to not order ‘jawanoko jhol” (for nursing females only, helps let down), I am told this will be explained soon in private. Curiosity grew. This hospital tour has surprised me because what I had in mind was a hospital with few rooms with barely any equipment. On the contrary, Patan hospital is fairly well equipped and organized with a CT scanner, multiple wards, and the medical school has an extensive public health department. Meanwhile I am offered a tea and biscuit everywhere. My first few hours of touring showed me that this is going to be a fun experience. This is followed by a stop at the Intensive Care Unit (ICU) where I will be on rotation for the next few weeks. Another cup of tea and biscuit follows, fourth of the day already. Day one starts in ICU with meeting medical officers, staff, patients and nurses. Talking to patients helps me learn their perspective. It is quick mixing up with medical officers through lunch strolls, breaks. Our lunch discussions are very interesting, sharing our knowledge and experiences about our culture and educational system. What struck me then is I read and hear so much about what visitors have to say and how extraordinarily helpful this experience has been in shaping their career.1 But I wonder what it’s like for the local officers, what’s the impact on the medical officers, residents and students. Is it helpful? Do they feel they learn something, positive or negative impact? Or is it a source of brain drain?